PENGARUH PENGGUNAAN APLIKASI WORDWALL DAN PEMBERIAN REWARD TERHADAP MOTIVASI MENGHAFAL JUZ AMMA - Nurhanisa Ridwan; Sitti Jamilah Amin; Buhaerah (Program Pascasarjana, UIN Alauddin Makassar, 2024)
This thesis discusses the use of the Wordwall application, the provision of rewards, and memorizing Juz Amma at SDN 88 Parepare. The main issue is whether there is a significant effect between the use of the Wordwall application and the provision of rewards on memorization motivation for Juz Amma. This research was conducted at SDN 88 Parepare with the aim of examining the relationship between memorization motivation for Juz Amma and the use of the Wordwall application and providing rewards. This study uses an associative type of research with a correlational research design. The research population consists of 106 students, with 84 samples selected using simple random sampling. Data collection techniques include observation, questionnaires, and documentation. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis techniques. The research findings concluded that: (1) The relationship between the use of the Wordwall application and memorization motivation for Juz Amma at SDN 88 Parepare is 31.5%, which falls under the low category. (2) The relationship between providing rewards and memorization motivation for Juz Amma at SDN 88 Parepare is 64.1%, which is classified as strong. (3) There is a significant effect between the use of the Wordwall application and the provision of rewards on memorization motivation for Juz Amma, as shown by the F-test, where the Significance value is 0.000 < 0.05, meaning H0 is rejected and H1 is accepted, with an influence contribution of 41.2%. The uniqueness of this study lies in the combination of the Wordwall application and the provision of rewards in the context of memorizing Juz Amma. This research is beneficial in the field of education, where technology used for memorizing Juz Amma can increase student engagement, thus helping to improve the quality of Islamic education.